2020
DOI: 10.1182/blood-2020-136583
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Brentuximab Vedotin As Monotherapy or in Combination for Older Hodgkin Lymphoma Patients

Abstract: Introduction: Older patients with classical Hodgkin lymphoma (cHL) have poor outcomes relative to younger patients, often due to comorbidities and toxicities related to standard first-line (1L) chemotherapy (5-yr PFS: 30%-45% vs 75%-80%) (Evens 2008; Proctor 2009). Brentuximab vedotin (BV), a CD30-directed antibody-drug conjugate, has robust activity in patients refractory to several lines of chemotherapy. Methods: This phase 2, open-label study, SGN35-015 (NCT01716806), evaluated efficacy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Median PFS and OS had not been reached in the nivolumab arm, with median follow up 19.4 months. 26 The authors concluded that brentuximab vedotin plus dacarbazine or nivolumab were reasonable combinations in this more unfit/frail patient population. The nivolumab combination was associated with a higher rate of Grade ≥ 3 treatment-related adverse events compared with the dacarbazine combination (60% vs 37%), including peripheral neuropathy (35% vs 26%), but a lower rate of serious treatment-related adverse events (5% vs 11%) and treatment discontinuations due to adverse events (30% vs 42%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Median PFS and OS had not been reached in the nivolumab arm, with median follow up 19.4 months. 26 The authors concluded that brentuximab vedotin plus dacarbazine or nivolumab were reasonable combinations in this more unfit/frail patient population. The nivolumab combination was associated with a higher rate of Grade ≥ 3 treatment-related adverse events compared with the dacarbazine combination (60% vs 37%), including peripheral neuropathy (35% vs 26%), but a lower rate of serious treatment-related adverse events (5% vs 11%) and treatment discontinuations due to adverse events (30% vs 42%).…”
Section: Discussionmentioning
confidence: 99%
“…Brentuximab vedotin has also been assessed as monotherapy and in combination with bendamustine, dacarbazine or nivolumab. 15,17,25,26 Importantly, patients enrolled in this study were ineligible for frontline conventional chemotherapy combinations (via investigator's judgement). Initial assessment of brentuximab vedotin monotherapy demonstrated promising efficacy with 92% of patients (median age 78 years) achieving an ORR (CR: 73%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BV monotherapy has been addressed in three different trials [ 65 , 66 , 67 ]. The data obtained show limited activity of BV monotherapy, warranting its use in combination regimens.…”
Section: The Use Of Novel Agents In the Treatment Of Elderly Patients...mentioning
confidence: 99%
“…A high discontinuation rate was observed due to AEs, mainly peripheral neuropathy (PN). The same study examined the role of adding bendamustine; however, due to unacceptable toxicity and high TRM, this arm was terminated early [ 67 , 68 ]. The HALO trial also examined the use of the latter regimen in 49 frail patients [ 69 ].…”
Section: The Use Of Novel Agents In the Treatment Of Elderly Patients...mentioning
confidence: 99%